O bem viver: uma experiência em comunidade indígena - Silva, Luiz Mendes da (2019)
This master thesis analyzes Bem Viver in the indigenous community in the municipality of Mangueirinha, in southwest of Paraná, seeking aspects of Bem Viver. The investigation brings as a research problem the question: are there elements of Bem Viver in the indigenous community? As a general objective, we chose to investigate the presence of Bem Viver in the local indigenous community, starting from the hypothesis that, for many years, Bem Viver was part of the Indians’ life, their traditions, and their habits. The specific objectives were to identify the elements that are part of the Culture of Bem Viver in specialized literature, followed by an observation in the indigenous community, searching to identify if those elements are in the indigenous community. This is a qualitative research, an exploratory one, based on the method of observation and data collection through Geertz's dense description method, a research with ethnographic features, through direct and indirect observation in the local Indigenous culture. Data were collected through observations and recorded in field diaries. For the theoretical methodological support we used the contributions of Acosta (2016), Geertz (2008) and Malinoviswki (1978). The present investigation found in the indigenous community of Mangueirinha, elements and aspects that resemble the elements of the philosophy of Good Living, especially in the aspects that involve the community life, being preserved and cultivated by the community through its daily practices, beliefs, rituals and Celebrations, especially the way of life of the elderly population of the community, in these, we observe the preservation of the philosophy of life of the Indian and the elements and characteristics that integrate the philosophy of Good Living.